2016
DOI: 10.1016/j.mce.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal effects of growth hormone and insulin-like growth factor-I therapy

Abstract: The growth hormone/insulin-like growth factor (GH/IGF) axis is critically important for the regulation of bone formation, and deficiencies in this system have been shown to contribute to the development of osteoporosis and other diseases of low bone mass. The GH/IGF axis is regulated by a complex set of hormonal and local factors which can act to regulate this system at the level of the ligands, receptors, IGF binding proteins (IGFBPs), or IGFBP proteases. A combination of in vitro studies, transgenic animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 249 publications
1
20
0
3
Order By: Relevance
“…Defective periosteal bone growth occurred in males and females and was therefore unlikely to be caused by sex hormones. IGF-1 signaling can affect bone width (Lindsey and Mohan, 2016), but Bmp2 Prx1-cKO mice expressed IGF-1 in bone (Figure 1—figure supplement 1a) and circulating IGF-1 was statistically unchanged in Bmp2 Prx1-cKO mice (Figure 1—figure supplement 1b). During ex vivo organ culture, WT and Bmp2 Prx1-cKO metatarsals were equal in length on day one and both grew in culture (Figure 1n).…”
Section: Resultsmentioning
confidence: 99%
“…Defective periosteal bone growth occurred in males and females and was therefore unlikely to be caused by sex hormones. IGF-1 signaling can affect bone width (Lindsey and Mohan, 2016), but Bmp2 Prx1-cKO mice expressed IGF-1 in bone (Figure 1—figure supplement 1a) and circulating IGF-1 was statistically unchanged in Bmp2 Prx1-cKO mice (Figure 1—figure supplement 1b). During ex vivo organ culture, WT and Bmp2 Prx1-cKO metatarsals were equal in length on day one and both grew in culture (Figure 1n).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials for several of the molecules mentioned above are currently undertaken. These include IGF-1, which has showed that it increased BMD and is reviewed by Lindsey RC et al [ 123 ]. Osteocalcin, irisin, myostatin could be also targets for future trials in order to become drugs for both osteoporosis and sarcopenia treatments (for detailed review on these, see [ 124 ]).…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“… 23 The synthesis of IGF-1 by osteoblasts is under the control of growth hormones and a deficiency of the growth hormone (GH)/IGF axis contributes to the development of low bone mass. 24 Our meQTLs-based gene set enrichment analysis reported significant associations between this gene set and the femoral neck and lumbar spine BMD. We also identified significant associations between Reactome GH receptor signalling and BMD in both the femoral neck and the lumbar spine, suggesting that genetically controlled methylation of the GH/IGF axis may play a critical role in bone metabolism.…”
Section: Discussionmentioning
confidence: 78%